2023
DOI: 10.3390/brainsci13071082
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Levels and Cognitive Decline following Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Cognitive decline (CD) is devastating with a high incidence in patients after stroke. Although some studies have explored underlying associations between C-reactive protein (CRP) levels and cognitive decline after stroke, consistent results have not been obtained. Therefore, this meta-analysis aimed to explore whether or not higher levels of C-reactive proteins were associated with an increased risk of cognitive decline after stroke. To this end, PubMed, Embase, the Cochrane Library, and Web of Science were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…An increased number of studies have investigated the expression of biomarkers such as C-reactive protein (CRP), interleukin 6 (IL-6), and interleukin 10 (IL-10). In 2023, a Meta-Analysis that involved nine studies with 3,893 participants showed the concentrations of peripheral CRP, especially in the acute stroke phase, are significantly increased for patients with cognitive decline after stroke compared to the patients without cognitive decline ( Wang et al, 2023 ). A prospective study conducted in 2022 that involved 1,003 stroke patients indicated elevated IL-6 levels were independently linked to a decline in MoCA scores following ischemic stroke and transient ischemic attack (TIA) ( Wang et al, 2022 ).…”
Section: Molecular Markers and Genetic Contributionsmentioning
confidence: 99%
“…An increased number of studies have investigated the expression of biomarkers such as C-reactive protein (CRP), interleukin 6 (IL-6), and interleukin 10 (IL-10). In 2023, a Meta-Analysis that involved nine studies with 3,893 participants showed the concentrations of peripheral CRP, especially in the acute stroke phase, are significantly increased for patients with cognitive decline after stroke compared to the patients without cognitive decline ( Wang et al, 2023 ). A prospective study conducted in 2022 that involved 1,003 stroke patients indicated elevated IL-6 levels were independently linked to a decline in MoCA scores following ischemic stroke and transient ischemic attack (TIA) ( Wang et al, 2022 ).…”
Section: Molecular Markers and Genetic Contributionsmentioning
confidence: 99%
“…The secretion of IL-17 by T cells leads to the production of chemokines from peripheral medullary cells (monocytes and neutrophils), thereby damaging the blood-brain barrier and inducing neuroinflammation, which exacerbates ischemic brain injury (Samuelson et al, 2019;Wang et al, 2022). In addition, intestinal microorganisms enter the circulation and extraintestinal organs, leading to local and systemic infections (Wang et al, 2023b).…”
Section: Gut Microbiota and Ismentioning
confidence: 99%
“…infection (PSI), which impact disease prognosis, resulting in progressive neurological deficits and high mortality (Lindner et al, 2019;Ułamek-Kozioł et al, 2020;Huang et al, 2022;Zhang et al, 2022;Hede Ebbesen et al, 2023;Wang et al, 2023b).…”
mentioning
confidence: 99%